The politics of order in informal markets : how the state shapes private governance - Grossman, Shelby (Cambridge : Cambridge University Press, 2021)
Property rights are important for economic exchange, but many governments don't protect them. Private market organizations can fill this gap by providing an institutional structure to enforce agreements, but with this power comes the ability to extort group members. Under what circumstances, then, will private organizations provide a stable environment for economic activity? Based on market case studies and a representative survey of traders in Lagos, Nigeria, this book argues that threats from the government can force an association to behave in ways that promote trade. The findings challenge the conventional wisdom that private good governance in developing countries thrives when the government keeps its hands off private group affairs. Instead, the author argues, leaders among traders behave in ways that promote trade primarily because of the threat of government intrusion.
Title from publisher's bibliographic system (viewed on 09 Jul 2021).
Keywords: Informal sector (Economics) -- Developing countries; Economic policy -- Developing countries; Business and politics -- Developing countries; Private companies -- Developing countries